2019
DOI: 10.1155/2019/3513179
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in the Progress of Diabetic Nephropathy: A Systematic Review and Meta-Analysis

Abstract: Background. We conducted a systematic review and meta-analysis of existing literature to evaluate the different outcomes of microRNAs (miRNAs) in diabetic nephropathy (DN), including urinary albumin excretion rates, urinary albumin creatinine rates, glomerular filtration rate, HbAc1, and creatinine. Methods. Electronic databases including PUBMED, MEDLINE, and EMBASE were searched for eligible publications to July 2018. The following comparisons between treatment groups were included: normal group versus DN gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 32 publications
1
32
0
1
Order By: Relevance
“…Whereas, seven miRNAs were downregulated in DN, including miRNA-26a, miRNA-126, miRNA-574-3p, miR-155, and miR-192 (Wang et al, 2019b). Importantly, the UAE rates correlated with these six miRNAs expressions (miR-133b, miR-342, miR-30, miR-192, miR-194, and miR-215), urinary albumin-creatinine ratio associated with five miRNAs expressions (miR-192, miR-217, miR-15b, miR-34a, and miR-636), and the GFR correlated with twelve miRNAs expressions (Eissa et al, 2016b;Wang et al, 2019b).…”
Section: Micrornas In Renal Hypertrophy and Ecm Accumulationmentioning
confidence: 92%
See 2 more Smart Citations
“…Whereas, seven miRNAs were downregulated in DN, including miRNA-26a, miRNA-126, miRNA-574-3p, miR-155, and miR-192 (Wang et al, 2019b). Importantly, the UAE rates correlated with these six miRNAs expressions (miR-133b, miR-342, miR-30, miR-192, miR-194, and miR-215), urinary albumin-creatinine ratio associated with five miRNAs expressions (miR-192, miR-217, miR-15b, miR-34a, and miR-636), and the GFR correlated with twelve miRNAs expressions (Eissa et al, 2016b;Wang et al, 2019b).…”
Section: Micrornas In Renal Hypertrophy and Ecm Accumulationmentioning
confidence: 92%
“…MicroRNAs (miRNAs) are the most studied ncRNAs in renalassociated complications (Simpson et al, 2016) (Table 1). Recent systematic review and meta-analysis in 12 of previous DN human studies (Wang et al, 2019b), showed that 15 miRNAs were upregulated in DN, including miRNA-21, miRNA-181b, and miRNA-215. Whereas, seven miRNAs were downregulated in DN, including miRNA-26a, miRNA-126, miRNA-574-3p, miR-155, and miR-192 (Wang et al, 2019b).…”
Section: Micrornas In Renal Hypertrophy and Ecm Accumulationmentioning
confidence: 99%
See 1 more Smart Citation
“…lncRNAs act as competitive endogenous RNAs (ceRNAs) that competitively bind to miRNAs (18). Recent studies indicated that miRNAs are involved in DN pathogenesis, including microRNA-216a (miR-216a) (19,20). However, the relationship between ZEB1-AS1 and miR-216a-5p in DN development is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic nephropathy (DN), one of the most prevalent complications in diabetes, is characterized by a progressive development of renal dysfunction. In the early stage, the first symptom is microalbuminuria (appearance of low levels of albumin in the urine, 30-300 mg/g), which precedes macroalbuminuria (high levels of albumin in the urine, >300 mg/g), leading to a deterioration of renal function and progression to End Stage Renal Disease (ESRD) [64]. Accumulating evidence has clearly demonstrated that immune-inflammatory response plays a paramount role in the onset and progression of diabetic kidney disease.…”
Section: Diabetic Nephropathymentioning
confidence: 99%